Good, Bad, and Ugly Colonial Activities : Do They Matter for Economic Development? - Bruhn, Miriam; Gallego, Francisco A. (MIT Press, 2015)
Levels of development vary widely within countries in the Americas. We argue that part of this variation has its roots in the colonial era, when colonizers engaged in different economic activities in different regions of a country.We present evidence consistent with the view that “bad” activities (those that depended heavily on labor exploitation) led to lower economic development today than “good” activities (those that did not rely on labor exploitation). Our results also suggest that differences in political representation (but not in income inequality or human capital) could be the intermediating factor between colonial activities and current development.